The Effects of 5-Fluorouracil/Leucovorin Chemotherapy on Cognitive Function in Male Mice - Groves, Thomas; Corley, Christa; Byrum, Stephanie D.; Allen, Antiño R. (Frontiers in Molecular Biosciences, 2021)
5-Fluorouracil (5-Fu) and leucovorin (LV) are often given in combination to treat colorectal cancer. 5-Fu/LV prevents cell proliferation by inhibiting thymidylate synthase, which catalyzes the conversion of deoxyuridine monophosphate to deoxythymidine monophosphate. While 5-Fu has been shown to cause cognitive impairment, the synergistic effect of 5-Fu with LV has not been fully explored. The present investigation was designed to assess how the combination of 5-Fu and LV affect cognition in a murine model. Six-month-old male mice were used in this study; 15 mice received saline injections and 15 mice received 5-Fu/LV injections. One month after treatment, the elevated plus maze, Y-maze, and Morris water maze behavioral tasks were performed. Brains were then extracted, cryosectioned, and stained for CD68 to assay microglial activation and with tomato lectin to assay the vasculature. All animals were able to locate the visible and hidden platform locations in the water maze. However, a significant impairment in spatial memory retention was observed in the probe trial after the first day of hidden-platform training (first probe trial) in animals that received 5-Fu/LV, but these animals showed spatial memory retention by day 5. There were no significant increases in inflammation as measured by CD68, but 5-Fu/LV treatment did modulate blood vessel morphology. Tandem mass tag proteomics analysis identified 6,049 proteins, 7 of which were differentially expressed with a p-value of <0.05 and a fold change of >1.5. The present data demonstrate that 5-Fu/LV increases anxiety and significantly impairs spatial memory retention.